Die lewe en werk van Gerhard Ebeling (06 Julie 1912 – 30 September 2001): ŉ Leksikografiese bydrae tot Reformasie 500 - Wyk, Gabriël M. J.van (HTS teologiese studies, 2017)
Focusing on Ebeling’s own account of his ‘theological path’, autobiographical notes in hispublications and a gold mine of information in the biography of Albrecht Beutel on Ebelingpublished in 2012 the article describes important events with theological significance in lifeof Gerhard Ebeling. Ebeling is often portrayed in theological literature as a representativeof the so-called New Hermeneutic. For many people the name Ebeling is synonymous withhermeneutics, as if his only contribution to theology was the development of ‘a newhermeneutical theory’. This is a misconception. The article introduces the reader to anotherand more important point of view to value the life and work of Ebeling – his interest in theReformer Martin Luther, that not only had profound influence on Ebeling’s own theologicalthinking, but also resulted in many ground breakingpublications on Luther. The articlecelebrates Ebeling as one of the most important Luther scholars of all times.